Maternal serum lactate dehydrogenase level and adverse pregnancy outcomes in women with hypertensive disorder of pregnancy at a tertiary care centre: a retrospective study - Ajila, Disha; Raja, Aishwarya; Ganiga, Pradeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hypertensive disorder of pregnancy affect 6-8% of all pregnancies, contributing immensely to maternal morbidity and mortality. Thus, presence of lactate dehydrogenase (LDH) signifies tissue damage and haemolysis. The aim of the study was to correlate LDH levels with blood pressure ranges and maternal and foetal outcome in women with gestational hypertension, pre-eclampsia. Methods: This retrospective study was conducted in the department of obstetrics and gynaecology of AJ Institute of Medical Sciences and Research Centre, Mangalore for a period of 1 year (January 2020 to January 2021). Based on the eligibility criteria, 52 hypertensive pregnant women were enrolled as cases. Results: Mean±SD period of gestation at delivery was lowest (34.57±1.39 weeks) for pregnant women with S. LDH levels>800 IU/l, whereas with S. LDH<00 IU/l delivered at around 37 weeks of gestation. Mean Apgar scores were lowest for the babies born to hypertensive pregnant women>800 IU/l, mean±SD Apgar scores at the end of 1 min, 5 minutes and 10 min were 4.42±0.79, 4.75±2.26 and 5.50±2.65 respectively. Conclusions: It can be concluded that S. LDH has the potential to be considered as a screening tool or predictor of the outcome of pregnancy in women with hypertensive disorders of pregnancy. However, studies of larger magnitude may be required to confirm the presence and the strength of association of S. LDH levels with pregnancy outcome.